Prehospital advanced airway and ventilation management (PHAAM) in experimental trauma - Tomas Karlsson (2025)
Effective prehospital airway management is vital for trauma patients, where securing oxygen delivery, ventilation, and hemodynamic stability is critical yet complicated by airway obstruction and hypovolemia. This thesis evaluates alternative strategies when conventional endotracheal intubation and positive pressure ventilation are impractical or dangerous, using rigorous porcine trauma models to simulate real-world challenges. Study I showed that surgical cricothyroidotomy with the scalpel-bougie-tube method was faster and achieved superior oxygenation than percutaneous Seldinger-based cricothyroidotomy in obese trauma settings, highlighting its potential as the preferred emergency approach. Study II found that permissive hypoventilation maintained oxygen delivery on par with positive pressure ventilation following hemorrhage and resuscitation, suggesting it as a feasible priority when spontaneous breathing is intact. Study III demonstrated that expiratory ventilation assistance via a small-lumen catheter maintained oxygen delivery while reducing intratracheal pressures and lactate, offering a promising alternative in partial airway obstruction. Study IV showed that flow-controlled ventilation with an I:E ratio of 1:1 using 21% oxygen restored oxygenation and ventilation during total airway obstruction more effectively than higher I:E ratios, which caused negative intratracheal pressures. Overall, these findings support a physiology-guided, enhanced airway strategy in trauma care, emphasizing a surgical front-of-neck access in obese patients, permissive hypoventilation to protect hemodynamics, and flow-controlled or expiratory ventilation techniques as potential rescue interventions, thereby advancing prehospital trauma protocols toward adaptable, evidence-based solutions that can be applied swiftly under austere conditions.List of scientific papersI. Comparison of emergency surgical cricothyroidotomy and percutaneous cricothyroidotomy by experienced airway providers in an obese, in vivo porcine haemorrhage airway model. Karlsson T, Brännström A, Gellerfors M, Gustavsson J, Günther M. Mil Med Res. 2022;9(1):57 https://doi.org/10.1186/s40779-022-00418-8II. Permissive hypoventilation is equally effective to maintain oxygenation as positive pressure ventilation after porcine class III hemorrhage and whole blood resuscitation. Karlsson T, Gellerfors M, Gustavsson J, Günther M. Transfusion 2023;63(S3):S213-S221 https://doi.org/10.1111/trf.17344III. Expiratory ventilation assistance versus pressure-controlled ventilation with ambient oxygen in a hemorrhagic trauma model: a prehospital rescue option? Karlsson T, Gustavsson J, Wellfelt K, Günther M. Intensive Care Med Exp. 2025;13(1):31 https://doi.org/10.1186/s40635-025-00742-yIV. Optimizing flow-controlled ventilation: impact of I:E ratios and oxygen concentration in a porcine model of total airway obstruction. Karlsson T, Gustavsson J, Wellfelt K, Günther M. Anesth Analg. 2025 May 16 https://doi.org/10.1213/ANE.0000000000007583